Use of Malyugin pupil expansion device for intraoperative floppy-iris syndrome: results in 30 consecutive cases - Chang, David F (Journal of cataract and refractive surgery, 2008)
To evaluate a new disposable, small-pupil expansion device in tamsulosin patients with intraoperative floppy-iris syndrome (IFIS) having cataract surgery. Private practice, Los Altos, California, USA. The 5-0 polypropylene Malyugin pupil expansion device (MicroSurgical Technology) was used in 30 eyes from 21 tamsulosin patients having routine cataract surgery. The pupil diameter was measured at the beginning and end of surgery, and the severity of IFIS was graded. Intraoperative and postoperative complications were recorded. The device maintained a constant 6.0 mm pupil diameter throughout surgery. Although iris prolapse was still possible, there were no significant intraoperative or postoperative complications despite the fact that 93% of the eyes had moderate to severe IFIS. All eyes achieved a best corrected visual acuity of at least 20/25. There was a tendency for ring deformation if flash sterilization was used without sufficient cooling time. The disposable Malyugin pupil expansion device was highly effective at maintaining an adequate pupil opening in eyes with IFIS. It is easier and faster to use than iris retractors and other pupil expansion rings and represents an excellent small-pupil strategy.